Identifikasi Tingkat Ketercapaian Kota Ramah HAM Ditinjau dari Hak Warga Kota berdasarkan Persepsi Masyarakat: Studi Kasus Kecamatan Coblong - Fitria Dwi Rahman; Ira Safitri Darwin (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. One of the human rights protected by the government is the rights of urban people. Can access all public facilities and utilities without exception. As one of the embodiments of SDG's and NUA. Cities should be enjoyed and used by everyone. The city of Bandung is one of the human rights-friendly cities in Indonesia that upholds the rights of its citizens. After five years running, the charter of the declaration of a human rights-friendly city has been questioned. Most residents do not know that the city of Bandung has the status of a human rights-friendly city. Therefore, the authors identify the level of achievement of a human rights-friendly city so that they can provide input in optimizing government efforts that play a role in fulfilling the basic rights of citizens. And what causes this human rights-friendly city to fail. By using an empirical approach and a mix method as well as djanalysis using a Rasch model to see the level of achievement and defining factor. From the results of the analysis, it is found that this Human Rights-friendly city is highly realized because the rights of the city's citizens are fulfilled. It's just that the less than optimal socialization also affects the lack of community participation. In the research conducted, hopefully it can be used as input for the government to re-socialize a human rights-friendly city in the city of Bandung. Abstrak. Hak asasi manusia yang dilindungi pemerintah salah satunya adalah hak asasi masyarakat kota. Dapat mengakses semua fasilitas dan utilitas publik tanpa terkecuali.sebagai salah satu perwujudan SDG’s dan NUA. Kota harus dinikmati dan dimanfaatkan oleh semua orang. Kota Bandung menjadi salah satu kota ramah HAM di Indonesia yang menjunjung tinggi hak warga kota nya. Setelah lima tahun berjalan, piagam deklarasi kota ramah HAM tersebut dipertanyakan. Sebagian besar warga tidak mengetahui bahwa Kota Bandung menyandang status kota ramah HAM. Maka dari itu penulis mengidentifikasi tingkat ketercapaian kota ramah HAM agar bisa memberikan masukan dalam pengoptimalan upaya pemerintah yang berperan sebagai pemenuhan hak dasar warga. Serta apa yang menyebabkan kota ramah HAM ini tidak berhasil. Dengan menggunakan pendekatan empiris dan mix method serta djanalisis menggunakan rasch model agar terlihat tingkat ketercapaian dan faktor penentu. Dari hasil analisis didapatkan bahwa kota Ramah HAM ini terealisasi tinggi karena hak warga kota yang terpenuhi. Hanya saja sosialisasi yang kurang maksimal mempengaruhi pula kurangnya partisipasi wasyarakat. Dalam penelitian yang dilakukan semoga bisa menjadi bahan masukan kepada pemerintah untuk mensosialisasikan kembali kota ramah HAM di Kota Bandung.